دراسة مقارنة بين بيان الشعب الجزائري 1943 م ووثيقة الإستقلال المغربية 1944 م - (:unkn) unknown (جامعة الوادي university of Eloued, 2021)
ملخص : إن ظروف الحرب العالمية الثانية وما نتج عنها من تأثيرات على الحركتين الوطنيتين الجزائرية والمغربية من نشر الوعي الوطني وتغيير المطالب من إصلاحية الى المطالبة بالاستقلال، خلال هذه الظروف نجد الجزائر قد أصدر بيان 10 فيفري1943م او بيان الشعب الجزائري قام بتحريره فرحات عباس وقد شارك فيه كل التيارات الوطنية جمعية العلماء المسلمين، وحزب الشعب الجزائري، المنتخبين المسلمين وشخصيات وطنية ... وقاموا بتقديم نسخة منه الى السلطات الفرنسية ونسخة الى الحلفاء. ويعد بيان الشعب الجزائري نهاية مرحلة الفراغ السياسي الذي ساد منذ اندلاع الحرب العالمية الثانية، ويعد البيان خطوة مهمة في تطور الحركة الوطنية الجزائري وتبلور مطالبها. أما وثيقة المطالبة بالاستقلال المغربية أو بيان 11 يناير 1944 هو إحدى المحطات الرئيسية في تاريخ الكفاح الوطني الذي خاضه العرش والشعب المغربي من أجل الحرية والانعتاق من رقبة الاستعمار. قام رجال الحركة الوطنية بتنسيق مع الملك محمد الخامس، بخوض معركة نضالية حاسمة. تمثلت في تقديم وثيقة المطالبة بالاستقلال إلى سلطات الحماية الفرنسية وتسليم نسخ منها إلى المقيم العام غابرييل بيو وإلى القنصلين العامين لبريطانيا العظمى والولايات المتحدة وإلى الجنرال ديغول وسفير الاتحاد السوفيتي بالجزائر الفرنسية. وكان رد سلطات الحماية الفرنسية بشن حملة اعتقالات بعد أيام من تقديم الوثيقة. والضغط على السلطان محمد الخامس للتنديد علنا بالبيان. حيث ضربت موجة كبيرة من الاعتقالات الموقعين على الوثيقة، ومن بينهم أحمد بلافريج أمين عام حزب الاستقلال، هزت المظاهرات والاحتجاجات والانتفاضات البلاد، مما أدى إلى غضب شعبي عارم وإدانة شديدة في صفوف الشعب والموقعين على البيان لتأجج موجة شعبية لم تجد نهايتها إلا مع نهاية الحماية والاستقلال السياسي للمغرب. الكلمات المفتاحية: بيان الشعب الجزائري ، وثيقة الاستقلال المغربية ، المطالبة بالاستقلال ، حق الشعوب في تقرير المصير ، الحلفاء ، الحرب العالمية الثانية ، فرحات عباس ، أحمد بلافريج . Summary: The conditions of the Second World War and the resulting effects on the Algerian and Moroccan national movement, such as spreading national awareness and changing demands from reform to demanding independence, led to the issuance of the February 1943 statement or the Algerian people’s statement on 10 February 1943, which was edited by Farhat Abbas and all national currents participated in it ( The Association of Scholars and the Algerian People's Party, elected Muslims, students...and several national figures). They submitted a copy to the French authorities and a copy to the Allies. The Algerian people's statement is the end of the political vacuum that has prevailed since the outbreak of World War II, and the statement is an important step in the development of the Algerian national movement and the crystallization of its demands. As for the Moroccan Declaration of Independence, or the 11January, 1944 manifesto, it is one of the main stations in the history of the national struggle waged by the Moroccan throne and people for freedom and emancipation from the neck of colonialism. The men of the national movement, in coordination with King Mohammed V, fought a decisive battle. It consisted in presenting the document claiming independence to the French protectorate authorities and handing copies of it to the Resident General Gabriel Beau, to the Consuls General of Great Britain and the United States, to General de Gaulle and the Ambassador of the Soviet Union in French Algeria. The response of the French protection authorities was to launch a campaign of arrests days after the document was submitted. And pressure on Sultan Mohammed V to publicly denounce the statement. Where a large wave of arrests hit the signatories to the document, including Ahmed Blafrij, Secretary-General of the Independence Party, the demonstrations, protests and uprisings shook the country, which led to massive popular anger and strong condemnation among the people and the signatories to the statement, fueling a popular wave that did not find its end except with the end of protection and independence. Morocco's political key words : Manifesto of the Algerian People, Proclamation of Independence of Morocco, Claiming independence, The Allies, The right of a people to self-determination, Order of 7 March 1944, Second World War, Farhat Abbas, Ahmed Blafrij.
مذكرة ماستر تاريخ تخصص تاريخ المغرب العربي المعاصر
Keywords: بيان الشعب الجزائري، وثيقة الإستقلال المغربية; La déclaration du peuple algérien, la déclaration d'indépendance du Maroc; The Algerian People's Declaration, the Moroccan Declaration of Independence